2019
DOI: 10.3390/en12030346
|View full text |Cite
|
Sign up to set email alerts
|

N-Doped Porous Carbon from Sargassum spp. as Efficient Metal-Free Electrocatalysts for O2 Reduction in Alkaline Fuel Cells

Abstract: This work reports the synthesis of N-doped porous carbon (NPC) with a high surface area from Sargassum spp. as a low-cost alternative for electrocatalyst production for the oxygen reduction reaction (ORR). Sargassum spp. was activated with potassium hydroxide at different temperatures (700, 750, and 800 °C) and then doped with pyridine (N700, N750, and N800). As a result of the activation process, the 800 °C sample showed a high surface area (2765 m2 g−1) and good onset potential (0.870 V) and current density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…All the samples displayed characteristic D and G band in the corresponding Raman spectra, where D band represents defective sp 3 domain and G band represents ordered sp 2 domains. [46] It is observed that with increase in the calcination temperature from 300 to 500 °C, the I D /I G ratio of the N-doped carbon decreases from 1.03 to 0.69. However, further increase in the calcination temperature to 600 °C resulted in higher I D /I G ratio (0.87), indicating collapse of ordered structure at relatively higher temperature (Supporting info, Table S1).…”
Section: Characterization Of the Materialsmentioning
confidence: 94%
“…All the samples displayed characteristic D and G band in the corresponding Raman spectra, where D band represents defective sp 3 domain and G band represents ordered sp 2 domains. [46] It is observed that with increase in the calcination temperature from 300 to 500 °C, the I D /I G ratio of the N-doped carbon decreases from 1.03 to 0.69. However, further increase in the calcination temperature to 600 °C resulted in higher I D /I G ratio (0.87), indicating collapse of ordered structure at relatively higher temperature (Supporting info, Table S1).…”
Section: Characterization Of the Materialsmentioning
confidence: 94%
“…Sargassum can be used to obtain biocarbon and nanocarbon for the generation of electrocatalysts and specialized goods for high-tech industries. It has also shown great potential for the green synthesis of metal nanoparticles with multiple applications [85][86][87].…”
Section: Advanced Materialsmentioning
confidence: 99%
“…Sargassum aqueous extracts for electrocatalysts and the synthesis of platinum, gold and silver nanoparticles that can be used in the construction of electrochemical glucose sensing platforms, in the catalytic activity for blue methylene degradation and as antibacterials for Staphylococcus aureus and Pseudomonas aeruginosa) [85][86][87][101][102][103] Bioremediation and purification mechanisms Effectiveness of a Sargassum-based bioremediation system for the removal of metal ions and toxic dyes in water [104] 3.2.6. Regulations and Other Strategic Lines…”
Section: Advanced Materialsmentioning
confidence: 99%
“…Pelagic Sargassum chemical composition opens the opportunity to develop new nanostructured tailored materials for multiple applications, such as energy generation [142,143], medicine [144], antibacterial agents [145,146], and environmental remediation tools [147,148]. Recently, nanocarbons materials have been produced from brown sargassum for their use in electrochemical systems such fuel cells as [142] and supercapacitors [149], where the algae was activated at different temperatures presenting high specific surface areas <2500 m 2 /g. In the case of the alkaline fuel cell, the oxygen reduction reaction parameters of the nitrogen-doped carbon show comparable results with the traditional Pt electrocatalyst material [142].…”
Section: Nanostructured Materialsmentioning
confidence: 99%
“…Recently, nanocarbons materials have been produced from brown sargassum for their use in electrochemical systems such fuel cells as [142] and supercapacitors [149], where the algae was activated at different temperatures presenting high specific surface areas <2500 m 2 /g. In the case of the alkaline fuel cell, the oxygen reduction reaction parameters of the nitrogen-doped carbon show comparable results with the traditional Pt electrocatalyst material [142].…”
Section: Nanostructured Materialsmentioning
confidence: 99%